Level of sustainability awareness: where are the students' positions?. Issue 1 (March 2021) - Ridwan, I M; Kaniawati, I; Suhandi, A; Samsudin, A; Rizal, R
Abstract: Education for sustainable development (ESD) is a concern for not only Indonesian government but also worldwide. To create sustainable education, every individual has the responsibility to keep ESD as valuable capital for today's and future generations. The aim of this study to get information on the level of awareness about sustainability in protecting planet Earth. In addition, This study aims to work out the extent of sustainable awareness within the concept of sustainable development education among pre-service physics teacher based on gender at one of the universities in Tasikmalaya. Data collection was administered employing a closed questionnaire. The results showed that the sustainability awareness of students with an average value of 0.77 was in the high criteria. However, the sustainability practice awareness category includes the standards of rarely done . In addition, the sustainability awareness of female students is relatively higher compared to male students with percentage ratio of 78.1% and 75.5%. In conclusion, although they have a high level of sustainability awareness, students are "still less effective" in the category of "sustainability practice awareness with performance" and "practice some attitudes in making practices that support sustainable development".